2018
DOI: 10.1016/j.ecolind.2018.03.066
|View full text |Cite
|
Sign up to set email alerts
|

Clarifying some assumptions of coastal management: Analysis of values and uncertainties embedded in beach quality indexes

Abstract: For the first time, this research addresses the assessment of the quality of knowledge embedded in beach quality indexes from a socioecological perspective. We took the most widespread beach quality indexes and identified, selected and assessed the most important existing assumptions. We scored the robustness of these assumptions, using an inclusive methodology (stakeholder meeting, four focus groups and an online questionnaire). The NUSAP criteria for assessing the value-ladenness of scientific studies (Influ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…for sustainable management (Ariza et al, 2010;Botero et al, 2015;Semeoshenkova et al, 2015;Lucrezi et al, 2016;Rodella et al, 2017a;Bombana and Ariza, 2018). Among others, Anderies et al (2004) and McLachlan et al (2013) indicated four main interrelated elements that occurred for sustainable management of SES: (i) the physical beach i.e.…”
mentioning
confidence: 99%
“…for sustainable management (Ariza et al, 2010;Botero et al, 2015;Semeoshenkova et al, 2015;Lucrezi et al, 2016;Rodella et al, 2017a;Bombana and Ariza, 2018). Among others, Anderies et al (2004) and McLachlan et al (2013) indicated four main interrelated elements that occurred for sustainable management of SES: (i) the physical beach i.e.…”
mentioning
confidence: 99%